Trucking, Owner-Operators, and Florida Perishables - Richard Beilock (EDIS)
In the early 1980s, owner-operators accounted for just over half of all interstate movements of Florida's produce/ornamentals (Beilock and Fletcher, 1983). During the past two decades, trucking deregulation and technological developments have favored larger carriers, which may have caused the importance of owner-operators to decline. In this report, we examine the extent to which owner-operators have been able to maintain their share of Florida's produce/ornamentals haulage and their dependence upon larger carriers to secure loads. his is EDIS document, FE543, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2005.